(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2013)
Although cognitive behavior therapies are vastly studied treatments for panic disorder, reviews on the subject usually don’t discriminate between individual and group settings. This article aims to evaluate, through meta-analytical techniques, the effectiveness of group cognitive behavior therapy for panic disorder. A literature search on LILACS, PsycINFO, ISI Web of Knowledge and Pubmed was conducted. Intra-group Hedges (g) effect size calculations were made for symptoms of panic and anxiety, agoraphobia, and depression. A random effects model was used to estimate the summary effect sizes and the publication bias was calculated. The search identified 22 articles from 14 different studies. Summary effect sizes were large for symptoms of panic and anxiety (g=1,39), moderate for symptoms of depression (g=0,79) and large for agoraphobic symptoms (g=0,92). These results suggest that these therapies in group are effective for panic disorder and constitute an interesting alternative of treatment.